2017
DOI: 10.3389/fmicb.2017.00466
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Salinity by Flooding an Extremely Alkaline and Saline Soil Changes the Bacterial Community but Its Effect on the Archaeal Community Is Limited

Abstract: Regular flooding of the soil to reduce salinity will change soil characteristics, but also the microbial community structure. Soil of the former lake Texcoco with electrolytic conductivity (EC) 157.4 dS m-1 and pH 10.3 was flooded monthly in the laboratory under controlled conditions for 10 months while soil characteristics were determined and the archaeal and bacterial community structure monitored by means of 454 pyrosequencing of the 16S rRNA gene. The EC of the soil dropped from 157.8 to 1.7 dS m-1 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 49 publications
2
17
1
Order By: Relevance
“…The relative abundance of Bacteroidetes , Chloroflexi , and Proteobacteria is comparably low in Witpan. The sequences related to Bacteroidetes Incertae Sedis – known as Rhodothermales and Cytophagia – can be classified within Bacteroidetes and have recently been identified in alkaline and saline soils ( de Leon-Lorenzana et al, 2017 ) as well as in microbial mats ( Fernandez et al, 2016 ). In pan sediments, the members of thermophilic Chloroflexi have been assigned to Dehalococcoidetes , which uses organohalide respiration for energy conservation ( Kaster et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of Bacteroidetes , Chloroflexi , and Proteobacteria is comparably low in Witpan. The sequences related to Bacteroidetes Incertae Sedis – known as Rhodothermales and Cytophagia – can be classified within Bacteroidetes and have recently been identified in alkaline and saline soils ( de Leon-Lorenzana et al, 2017 ) as well as in microbial mats ( Fernandez et al, 2016 ). In pan sediments, the members of thermophilic Chloroflexi have been assigned to Dehalococcoidetes , which uses organohalide respiration for energy conservation ( Kaster et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within Proteobacteria , most saline samples (16/23) were dominant by Gammaproteobacteria , and Arit S. de León-Lorenzana et al . 44 has observed a sharp relative abundance decrease of Gammaproteobacteria by flooding a saline soil, suggesting Gammaproteobacteria was more adaptive to saline environments than other proteobacterial classes. Moreover, it confirmed the widespread distribution of Halobacteria of Archaea , Proteobacteria of Bacteria in soils.…”
Section: Discussionmentioning
confidence: 99%
“…While multiple Corynebacterium species are notable human pathogens (Bernard, 2012), other research has identified isolates of this genus that are highly associated with sugarcane rhizosphere with increased soil salinity (Pirhadi, 2018). Phyllobacteriaceae and Streptococcaceae were also indicator groups for added Na and are bacterial families previously identified to be associated with high saline soil microbiomes (de León-Lorenzana et al, 2017;Genderjahn et al, 2018). Listeraceae and Propionibacteriaceae, additional indicator groups for added Na, are also families with species that are capable of growth in relatively high concentrations of Na (Labadie et al, 2003;Liu et al, 2005).…”
Section: Bacterial Communitiesmentioning
confidence: 97%